Analisis Determinan yang Mempengaruhi Persepsi Perawat terhadap Keselamatan Pasien di Rawat Inap RSKB Columbia Asia Pulomas Tahun 2025 - Atika Kharisma; Eka Yoshida; Ahdun Trigono (Pusat Riset dan Inovasi Nasional, 2025)
Patient safety is a primary concern for healthcare facilities. Nurses carry a crucial responsibility in safeguarding patient safety. This study aims to examine the determinants that influence nurses’ perceptions of patient safety in the inpatient wards of RSKB Columbia Asia Pulomas. The research employed a mixed-method sequential explanatory design, beginning with a quantitative study followed by a qualitative phase. The quantitative participants consisted of 64 inpatient nurses selected through total sampling, while the qualitative participants comprised 3 key informants chosen via purposive sampling. The quantitative instrument was a validated and reliable questionnaire, and the qualitative data were collected using a semi-structured interview guide. Quantitative data were analyzed using chi-square tests and multivariate logistic regression analysis. The chi-square results indicated that interpersonal communication (p=0.000), work motivation (p=0.000), attitude (p=0.000), scheduling (p=0.000), and handover processes (p=0.000) were significantly associated with patient safety. Meanwhile, the multivariate logistic regression revealed two statistically significant factors: handover (p=0.018), which increased the likelihood of good patient safety by 19.057 times, and attitude (p=0.039), which increased it by 16.6 times compared to poor patient safety. In contrast, interpersonal communication (p=0.913), motivation (p=0.782), and scheduling (p=0.998) were not significant after controlling for other variables. The qualitative findings reinforced the quantitative results. Based on this study, it is recommended to enhance the implementation of nurse handovers using the SBAR approach and to optimize positive nursing behaviors toward patient safety culture.